POWER AND MADNESS: A FOUCAULDIAN ANALYSIS OF INSTITUTIONAL CONTROL IN SHUTTER ISLAND - Maharani, Dhea Gladys; Nirmalawati, Widya (BASIS (Bahasa dan Sastra Inggris), 2025)
This study examines Michel Foucault's theories on power and madness through the film Shutter Island, focusing on how institutional control shapes perceptions of sanity and insanity. Using Madness and Civilization as a theoretical framework, the research explores how psychiatric institutions define and regulate madness, creating "docile bodies" through surveillance and discipline. The data source consists of selected scenes from Shutter Island that illustrate institutional control mechanisms. The study employs qualitative methods, including scene analysis and dialogue transcription, to uncover the film's depiction of power dynamics. The findings reveal that the institution on Shutter Island functions as both a physical and psychological prison, using isolation, sedation, and psychological manipulation to maintain authority over patients. The narrative critiques the normalization and pathologization of madness, demonstrating how compliance with institutional norms is rewarded while deviation is punished. Authority figures, particularly doctors, play a central role in shaping patients' realities, exposing the oppressive nature of psychiatric institutions disguised as therapeutic environments. This study offers a contemporary application of Foucault’s theories, highlighting the ethical implications of power in mental health care.